2007
DOI: 10.1590/s0100-879x2006005000191
|View full text |Cite
|
Sign up to set email alerts
|

Purification, partial characterization and role in lipid transport to developing oocytes of a novel lipophorin from the cowpea weevil, Callosobruchus maculatus

Abstract: Lipid transport in arthropods is achieved by highly specialized lipoproteins, which resemble those described in vertebrate blood. Here we describe purification and characterization of the lipid-apolipoprotein complex, lipophorin (Lp), from adults and larvae of the cowpea weevil Callosobruchus maculatus. We also describe the Lp-mediated lipid transfer to developing oocytes. Lps were isolated from homogenates of C. maculatus larvae and adults by potassio bromide gradient and characterized with respect to physico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…For the vitellin (the final storage form of vitellogenin in the oocyte) of two polychaetes, a lipid content of 16% and 50% has been reported (Baert et al 1984;Lee et al 2005). On the other hand, the non-sexspecific lipoproteins among the large lipid transfer proteins have also been shown to contribute to egg yolk, at least in crustacean (Lubzens et al 1997;Ravid et al 1999), insect Telfer et al 1991;Ximenes et al 2008), and chicken eggs (Steyrer et al 1990). In oocytes of some vertebrates (i.e., trout, frog, and hen) and in some insects, the incorporation of both yolk and lipoproteins is also evident from the presence of the corresponding receptors (Steyrer et al 1990;Cheon et al 2001 and references cited therein).…”
Section: Introductionmentioning
confidence: 99%
“…For the vitellin (the final storage form of vitellogenin in the oocyte) of two polychaetes, a lipid content of 16% and 50% has been reported (Baert et al 1984;Lee et al 2005). On the other hand, the non-sexspecific lipoproteins among the large lipid transfer proteins have also been shown to contribute to egg yolk, at least in crustacean (Lubzens et al 1997;Ravid et al 1999), insect Telfer et al 1991;Ximenes et al 2008), and chicken eggs (Steyrer et al 1990). In oocytes of some vertebrates (i.e., trout, frog, and hen) and in some insects, the incorporation of both yolk and lipoproteins is also evident from the presence of the corresponding receptors (Steyrer et al 1990;Cheon et al 2001 and references cited therein).…”
Section: Introductionmentioning
confidence: 99%
“…Lipoproteins from adult male (n=50) and female (n=25) lice were purified according to the procedure previously described in [ 22 , 56 , 57 ]. Briefly, male and female animals were homogenized separately in ice cold phosphate buffer saline (PBS; 0.10 M sodium phosphate, pH 7.0, and 0.15 M NaC1) in the presence of protease-inhibitor cocktail (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, they may have higher total lipid percentages than males, although it varies by species. Ximenes et al [104] with radioactive labeling studies, found fatty acids were used in egg production in C. maculatus females, Nwanze et al [94] found females contain more total lipids and triglycerides than males. It was determined that the total fatty acid amount in A. grandis adults was very low in the first four days of adult life and then increased with age [96], while the amount of lipids in the ovaries of T. molitor females increased during the first three days of adult life and then decreased [99].…”
Section: Sönmez Sinop Uni J Nat Sci 7(1): 81-101 (2022) Issn: 2536-4383mentioning
confidence: 99%